A Little View of The Indonesian Tax System - Gunadi Gunadi (LPPM-STPI, 2022)
Indonesia has come a long way in the last decade to improve its tax system in terms of both revenue generation and administrative efficiency. However, tax revenues are still low at 4,444 due to growing infrastructure spending and the need for social protection. With the exception of the natural resources sector, the best way to increase tax revenues is to expand the tax base and improve tax administration, rather than changing the size of taxes that appear more or less in line with international practice. Possible steps to expand the tax base include accepting more self-employed people in the tax system, targeting employer benefits and benefits, and reducing VAT exemptions. increase. Similarly, broad investment credit is not an ominous way to increase investment incentives over selective tax exemptions. The government plans to promote integration into the tax system in the long run, but the introduction of simplified tax systems to SMEs and SMEs is restricted by the government. Since 2002, tax administration has improved, internal control systems have improved, and administrative decision transparency has improved. New tax audits due to compliance risks in the resource sector, especially in income tax mining, could further improve the management system. This means that Indonesia now has access to international financial markets and a diverse portfolio of resources.